Freedom's teacher : the life of Septima Clark - Charron, Katherine Mellen (The University of North Carolina Press, 2009)
In the mid-1950s, Septima Poinsette Clark (1898-1987), a former public school teacher, developed a citizenship training program that enabled thousands of African Americans to register to vote and then to link the power of the ballot to concrete strategies for individual and communal empowerment. In this biography of Clark, Charron demonstrates Clark's crucial role--and the role of many black women teachers--in making education a cornerstone of the twentieth-century freedom struggle.